BIOPHYSICAL, BIOCHEMICAL AND MICROSCOPIC STUDIES ON WHOLE HISTONE GLYCATED BY DEOXYRIBOSE (Applied Biological Research, 2023)
Histones, upon reaction with reducing sugars, are known to generate highly  reactive advanced glycation end products (AGEs). In this study, we investigated the structural changes associated with the glycation of whole  histone by 2-deoxyD-ribose. The deoxy pentose was incubated with whole  histone for 12 days and the resultant biophysical and structural changes in  the deoxyribose modified-whole histone were investigated thoroughly using  biochemical assays, various spectroscopic techniques like UV-visible,  fluorescence, FT-IR, and CD, UPLC-MS, and transmission electron  microscopy. We found that deoxyribosylation of whole histone formed  ptosidine and Nε-carboxymethyl-L-lysine AGEs and was accompanied by  an increase in oxidative stress. The histone-AGEs caused gross structural  changes in the protein and formed large amorphous aggregates. The  presence of such AGE aggregates is likely to interfere with the proper  functioning of histones and chromatin, besides exhibiting immunogenicity  and generation oautoantibodies against nuclear antigens.
Keywords: 2-Deoxy-D-ribose; histones; mass spectrometry; Nε carboxymethyl-L-lysine; pentosidine; transmission electron microscopy